Audience response system (ARS) technology and dentist attendance in smoking cessation workshop - Kadir, R.A.; Siddiq, A.N.A.; Yahya, N.A.; Abd Rashid, Rusdi; Hazli, Z.; Hussain, H. (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study assess the effective use of audience response system (ARS), an interactive presenter-audience electronic system, in measuring Malaysian dentists' interest in attending a less explored non-clinical continuing professional education topic. A total of 157 dentists voluntarily attended a specially designed one-day-four-module workshop conducted in four urban locations. The effective use of ARS in commanding attendance was measured in terms of dentists' full seminar attendance to completion and opinion regarding the use of the instrument. The retention rate of workshop attendance to completion in the four locations ranged between 76.5 and 100. Out of these participants, 93.7 said they enjoyed the ARS approach, 92.4 agreed it motivated them to stay on until the end, 97 said it increased their curiosity and appreciates answering in anonymity. The use of ARS technology is effective in enhancing participants' interest and retention in the workshop, provides interactive learning opportunities and quick feedback and has a potential as an objective instrument in research data collection.